A critical analysis of barriers to the clinical implementation of pharmacogenomics - McKinnon, Ross A (Dove Medical Press, 2007)
Over recent decades, basic research has yielded a large volume of data on many potentially clinically relevant genetic determinants of drug efficacy and toxicity. Until recently, most examples involved genes encoding drug-metabolizing enzymes, particularly the cytochromes P450. More recently, rapid advances in genomic technologies have enabled broader, genome-wide searches for determinants of drug response. In parallel with these pharmacogenetic studies, a new drug discovery platform, termed pharmacogenomics, has emerged which utilises genetic information to guide the selection of new drugs most likely to survive increasingly demanding safety and efficacy assessments. Together, these advances are widely promoted as the basis of a new era of drug-based therapeutics tailored to the individual. The extent to which individualized or personalized medicine will emerge as a sustainable new therapeutic paradigm is, however, the topic of much debate. It is clear that an increasingly complex series of barriers must be overcome if we are to successfully harness genomic advances in the clinical setting. Potential barriers may include cost-effectiveness of the test, ethical concerns over the use of DNA, and required educational and equipment infrastructure. Although long overdue, many of these potential barriers are now being subjected to closer examination and as a result, a framework for successful clinical uptake of pharmacogenomics is emerging.